Nasal tip plasty using three-dimensional printed polycaprolactone (Smart Ball(®)) - Kim, Joo Hyoung (Yeungnam Univ J Med, 2019)
BACKGROUND: Rhinoplasty is one of the most commonly performed cosmetic surgery procedures. Most Asians desire elevation of their relatively flat nasal dorsum and tip to make them appear more prominent. This study introduces a simple method of nasal tip plasty using three-dimensional (3D)-printed polycaprolactone (PCL) (Smart Ball(®)), which provides the required length and volume for this purpose and enables the creation of a nasal tip of the desired shape in a safe and simple manner. METHODS: Between September 2014 and May 2017, 22 patients participated in a survey to assess postoperative satisfaction levels. Additionally, three plastic surgeons compared patients’ pre- and 1-year postoperative photographs to evaluate the results. All patients underwent 2- to 4-year postoperative follow-up. RESULTS: Levels of subjective satisfaction among patients were 3.59, 3.50, 3.82, 3.73, 3.55, and 3.82 for each of the 6 categories evaluated, with a mean of 3.67/4 points, indicating high satisfaction levels. The mean plastic surgeon-reported score for the 22 patients was 4.47/5 points, which also indicates highly successful outcomes. Postoperative nasal tip rotation and tip projection were ideal in most patients. CONCLUSION: Our novel method using 3D-printed PCL (Smart Ball(®)) provides the optimal length and volume required for nasal tip plasty and enables the creation of a nasal tip of the desired shape, in a safe and simple manner. An advantage of our method is that it retains the original nasal structure in contrast to structural changes observed with the use of conventional methods.